Art and Landscape Buddhist Rock Sculptures of Late Antique Swat/Uḍḍiyāna - Filigenzi, Anna (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
Buddhist rock sculpture of Swat/Uddiyana (7th-8th cent. CE): Analytical study of its aesthetic values, technical concept, historical background and cultural influence